Viral load kinetics and the clinical consequences of cytomegalovirus in kidney transplantation - Dobrer, Sabina; Sherwood, Karen R.; Hirji, Ishan; Lan, James; Gill, John; Matic, Nancy; Keown, Paul A. (Frontiers in Immunology, 2024)
Background: Despite advances in clinical management, cytomegalovirus (CMV) infection remains a serious complication and an important cause of morbidity and mortality following kidney transplantation. Here, we explore the importance of viral load kinetics as predictors of risk and potential guides to therapy to reduce transplant failure in a large longitudinal Genome Canada Transplant Consortium (GCTC) kidney transplant cohort.We examined the relationship between CMV infection rates and clinical characteristics, CMV viral load kinetics and graft and patient outcomes in 2510 sequential kidney transplant recipients in the British Columbia Transplant Program. Transplants were performed between January 1, 2008, and December 31, 2018, were managed according to a standard protocol and were followed until December 31, 2019, representing over 3.4 million days of care.Results: Longitudinal CMV testing was performed in 2464 patients of whom 434 (17.6%) developed a first episode of CMV viremia at a median of 120 (range: 9-3906) days post-transplant. Of these patients, 93 (21.4%) had CMV viremia only and 341 (78.5%) had CMV viremia with clinical complications, of which 21 (4.8%) had resulting hospitalization. A total of 279 (11.3%) patients died and 177 (7.2%) patients lost their graft during the 12 years of follow-up. Patients with CMV infection were at significantly greater risk of graft loss (p=0.004) and death (p=0.0006) than those without. Peak viral load ranged from 2.9 to 7.0 (median: 3.5) log₁₀ IU/mL, the duration of viremia from 2 to 114 (15) days, and the viral load area under the curve from 9.4 to 579.8 (9.7) log₁₀ IU/mL × days. All three parameters were closely inter-related and were significantly increased in patients with more severe clinical disease or with graft loss (p=0.001). Duration of the first CMV viremic episode greater than 15 days or a peak viral load ≥4.0 log10 IU/mL offered simple predictors of clinical risk with a 3-fold risk of transplant failure.Conclusions: Viral load kinetics are closely related to CMV severity and to graft loss following kidney transplantation and provide a simple index of risk which may be valuable in guiding trials and treatment to prevent transplant failure.